Reverse pharmacology: Searching for novel drugs in ticks and testing their effects on host immune cells - Kabrelian, Agop (Jihočeská univerzita, 2018)
The aim of this work is to use an approach of reverse pharmacology in searching for novel drugs from specific proteins, which are extracted from Ixodes ricinus salivary, and have pharmacoactive features that inhibit host haemostasis and modulate host inflammatory and immune responses.
Reverse pharmacology: Searching for novel drugs in ticks and testing their effects on host immune cells